1982
DOI: 10.1104/pp.70.5.1425
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Membrane-Bound Lectin in Developing Phaseolus vulgaris Cotyledons

Abstract: Cotyledons of developing Phaseolus vulgaris L. cv Greensleeves seeds were labeled for 2 to 3 hours with 3H-amino acids, and newly synthesized phytohemagglutinin (PHA) The existence of membrane-bound lectin in the organs ofhigher plants is still a matter of some controversy. Bowles et al. (6) reported that Triton X-100 extracts of membranes from leaves, shoots, and roots of soybean possess high hemagglutinating activity. Recently Pueppke et al. (12) re-examined the question and concluded that the only organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1984
1984
1994
1994

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…These results show that the [L38M, F94M, I96M1PHA mutant was efficiently transported in the secretory system. The rate of transport of [L38M,F94M,196MlPHA in these cells is similar to the rate of transport in bean cotyledons (Chrispeels and Bollini, 1982).…”
Section: Resultssupporting
confidence: 56%
“…These results show that the [L38M, F94M, I96M1PHA mutant was efficiently transported in the secretory system. The rate of transport of [L38M,F94M,196MlPHA in these cells is similar to the rate of transport in bean cotyledons (Chrispeels and Bollini, 1982).…”
Section: Resultssupporting
confidence: 56%
“…Sequestration into the lumen of the ER is followed by transport out of the ER with a half-life of -4 h. The kinetics of transport of rice lectin from the ER appear to be slower than those reported for legumin and vicilin in developing pea cotyledons (90 min) (Chrispeels et al, 1982a) and phytohemagglutinin in developing bean cotyledons (90 min) (Chrispeels and Bollini, 1982), but are of the same order of magnitude as those reported for a-amylase in barley aleurone layers (5 h) (Jones and Jacobsen, 1982), and are faster than those of pea lectin in pea cotyledons (6-8 h) (Higgins et al, 1983).…”
Section: Discussionmentioning
confidence: 92%
“…Experiments with peas, beans and castor beans indicate that in these seeds lectins are made on the rough endoplasmic reticulum (ER) as pre-pro-proteins which lose their signal sequence,when they are sequestered in the lumen of the ER. The proteins are then transported to the protein bodies where proteolytic processing occurs (Higgins et al, 1983;Chrispeels and Bollini, 1982;Roberts and Lord, 1981). In beans (Phaseolus vulgaris) this transport is mediated by the Golgi apparatus (Chrispeels, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…We explain these changes by proposing that, in summer, new tissue, which contains no lectin, is added to the bark from the inside while the cells in the outermost part degrade lectin, so that the total amount of lectin decreases. Biochemical studies have demonstrated that these proteins are synthesized on ERattached ribosomes and sorted into the ER lumen (Bollini and Chrispeels 1979;Bollini et al 1982;Chrispeels and Bollini 1982;; H u r k m a n and Beevers 1982; Faye and Chrispeels 1987), and it may be assumed that the bark lectin is also synthesized on ER-attached ribosomes. Our immunocytochemical data support this interpretation.…”
Section: Discussionmentioning
confidence: 99%